Vieillir hors couple : est-ce vieillir sans sexualité ? - Maïlys Goetschy; Hoël Berger; Brahim Benadouda; Aurélien Dasré; Julie Pannetier (Genre, Sexualité et Société)
The sexuality of single people over 50 years old is still too rarely studied due to a double blind spot in research: singlehood and the sexuality of older people. The major surveys on sexuality in France have clearly shown that despite a decrease in the frequency of sexual intercourse during life, 9 out of 10 people in a couple still have sexual relations after the age of 50. However, the sexuality of single people in their fifties, sixties and beyond remains to be questioned. Based on data from the 2016 Health Barometer, this article offers an analysis of the sexuality of single people over 50 by gender, age, socio-professional category and sexual orientation. The sexuality of people over 50 outside the couple is relatively frequent, although differentiated according to gender: one in three women has had at least one sexual intercourse in the year compared to two in three men. This difference increases with advancing in age, between 50 and 75, and higher position in the social hierarchy. Bisexual or homosexual single men maintain more frequently a sex life past 50 than exclusively heterosexual men.